Determinant Factors of The Frequency Of Fraud Occurance: Study on Sharia Banking in Indonesia - Abdullah Hasan, M Hadi Alamsyah; Any Eliza; Rahmat Fajar Ramdani; Ersi Sisdianto (Institut Agama Islam Negeri (IAIN) Madura, 2024)
This study investigates the determinant factors of the frequency of fraud on sharia banking in Indonesia. This study employed frequency of fraud occurance as dependent variable, quality of islamic corporate governance implemantation and bank complexity as independent variable. This research is a quantitative research with the type of data used, namely secondary data obtained from the official website of each bank and the OJK website. The data analysis used is multiple regression analysis using the E-Views 10 application. The results of this study show that partially the variable quality of the implementation of Islamic corporate governance has a positive effect on the frequency of fraud occurance and bank complexity does not have a significant positive effect on the frequency of fraud occurance.